War and political ethnography in Paita-Colán (1820-1823): A historical microanalysis about political space during the Hispanic monarchy crisis - Espinoza Claudio, César (2022)
The agricultural and political history of the province of Paita during the 19th century is still under academic study. San Lucas de Colán stands out in the coastal strip and currently lacks sociological research that studies its spatial formation, dynamics of land ownership, and regional political events. We take Peru’s bicentennial objectives as a framework to produce sociology and regional history knowledge. Also, we present a context to study several social actors providing information about the historical progress of a northern valley and rural population center during a viceregal Bourbon time that is transforming due to the complex processes for building a national republican state. We systematize ethnographic data by René Lesson. He was a French doctor and naturalist that arrived by chance at Colán beaches to collect botanical and zoological information. In addition, he reported the war between the Piura people and Spain, framed in a patriotic exaltation by the triumphal march of Santa Cruz with his Piuran battalion in Pichincha in 1822. The news of Bolivar’s arrival in March 1823 forced Lesson and his French companions to retreat hastily to Tahiti. This paper is based on the results of a SIN-SIN research project (2021) presented by the Research Group «Afrodescendants in Piura» and approved by the Vice Rectorate of Research and Postgraduate Research of the Universidad Nacional Mayor de San Marcos (VRIP-UNMSM).